Presepsin Levels in Pediatric Patients with Fever and Suspected Sepsis: A Pilot Study in an Emergency Department - Antonio Gatto; Lucia Mantani; Caterina Gola; Valeria Pansini; Lorenzo Di Sarno; Lavinia Capossela; Serena Ferretti; Benedetta Graglia; Antonio Chiaretti (MDPI AG, 2024)
Sepsis is a life-threatening condition that affects 1.2 million children annually. Although there are several criteria for diagnosing this condition, signs are often nonspecific, and identifying sepsis is challenging. In this context, presepsin (P-SEP) seems to be a promising new biomarker since its plasma levels increase earlier than other sepsis-related proteins and its measurement is faster. We enrolled 157 minors who presented to the Pediatric Emergency Department of Agostino Gemelli Hospital with fever and suspected sepsis. Biochemical, anamnestic, and clinical data were collected. Viral agents were identified as the causative factor in 64 patients, who had an average P-SEP value of 309.04 pg/mL (SD ± 273.2), versus an average P-SEP value of 526.09 pg/mL (SD ± 657) found in 27 bacterial cases (p value: 0.0398). Four cases of overt sepsis had an average P-SEP value of 3328.5 pg/mL (SD ± 1586.6). The difference in P-SEP levels in viral versus bacterial infections was found to be statistically significant; therefore, P-SEP may have a central role in the evaluation of febrile children, helping clinicians distinguish between these two etiologies. Furthermore, amongst the cases of confirmed sepsis, P-SEP was always greater than 2000 pg/mL, while C-reactive protein and procalcitonin values appeared lower than what was considered significant.